Analisis Nilai Perusahaan: Bukti Empiris pada Perusahaan Food and Beverage di Bursa Efek Indonesia - Farah Salsabila; Dhani Ichsanuddin Nur (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
This research aims to find out the impact of capital turnover on firm value moderated by profitability. In this research, the researcher uses a population of companies in the food and beverage division that have been listed on the IDX from 2016 to 2019. This research is quantitative. Researchers used purposive sampling as a sampling technique and used SPSS 22. Researchers used a sample of 16 companies over a four-year period. This research concludes that: 1) The replacement of working capital does not affect the value of the company. 2) The response between capital turnover and profitability has an effect on firm value. This statement tells that the variable of profitability can moderate the turnover of working capital to the company's score. Keywords: Working Capital Turnover, Firm Value and Profitability